Double dissociation between implicit and explicit personality self-concept: the case of shy behavior - Asendorpf, Jens B; Banse, Rainer; Mücke, Daniel (Journal of personality and social psychology, 2002)
Using the trait of shyness as an example, the authors showed that (a) it is possible to reliably assess individual differences in the implicitly measured self-concept of personality that (b) are not accessible through traditional explicit self-ratings and (c) increase significantly the prediction of spontaneous behavior in realistic social situations. A total of 139 participants were observed in a shyness-inducing laboratory situation, and they completed an Implicit Association Test (IAT) and explicit self-ratings of shyness. The IAT correlated moderately with the explicit self-ratings and uniquely predicted spontaneous (but not controlled) shy behavior, whereas the explicit ratings uniquely predicted controlled (but not spontaneous) shy behavior (double dissociation). The distinction between spontaneous and controlled behavior was validated in a 2nd study.